Setting the foundation: Uncovering potential constraints on the delivery and adoption of GM cotton in Uganda - Zambrano, Patricia; Falck-Zepeda, José B.; Sengooba, Theresa; Komen, John; Horna, Daniela (International Food Policy Research Institute, 2013)
The government of Uganda has already taken steps to evaluate and eventually commercialize genetically modified (GM) cotton. Uganda has drafted a Biotechnology and Biosafety Bill that is currently under parliamentary review. Meanwhile, the biophysical evaluation of insectresistant GM cotton is under way, and the two-year cycle of confined field trials has already been completed. However, a better agronomic performance of GM cotton relative to conventional cotton, under confined trials, may prove to be insufficient reason for decisionmakers to approve GM cotton in Uganda. In fact, the competent Ugandan authorities are now interested in evaluating the benefits of GM cotton adoption for cotton farmers and the overall economy. Although these socioeconomic considerations are not part of the Uganda Biosafety Bill, their implementation is under discussion.